Amphetamine acts within the lateral hypothalamic area to elicit affectively neutral arousal and reinstate drug-seeking. (29th July 2013) - Schmeichel, Brooke E.; Berridge, Craig W.
Abstract: Psychostimulants, including amphetamine (AMPH), exert robust arousal-enhancing, reinforcing and locomotor-activating effects. These behavioural actions involve drug-induced elevations in extracellular norepinephrine (NE) and dopamine (DA) within a variety of cortical and subcortical regions. The lateral hypothalamic area (LHA), including the lateral hypothalamus proper, perifornical area and adjacent dorsomedial hypothalamus, is implicated in appetitive- and arousal-related processes. The LHA is innervated by both NE and DA projections and systemically administered AMPH has been demonstrated to activate LHA neurons. Combined, these and other observations suggest the LHA may be a site of action in the behavioural effects of psychostimulants. To test this hypothesis, we examined the degree to which AMPH (10 nmol, 25 nmol) acts within the LHA to exert arousing, locomotor-activating and reinforcing actions in quietly resting/sleeping rats. Although intra-LHA AMPH robustly increased time spent awake, this occurred in the absence of pronounced locomotor activation or reinforcing actions, as measured in a conditioned place preference (CPP) paradigm. Arousing and stressful conditions or drug re-exposure can elicit relapse in humans and reinstate drug-seeking in animals. Given the LHA is also implicated in the reinstatement of drug-seeking behaviour, additional studies examined whether AMPH acts within the LHA to reinstate an extinguished CPP produced with systemic AMPH administration. Our results demonstrate that AMPH action within the LHA is sufficient to reinstate drug-seeking behaviour, as measured in this paradigm. Collectively, these observations demonstrate that psychostimulants act within the LHA to elicit affectively neutral arousal and reinstate drug-seeking behaviour.